Redesigning the Sputum Sample Container for TB Diagnosis to Minimize Aerosol Release and Decrease Manufacturing Material - Sanchez Sifuentes, M.; Wong Poggi, J.; Delgado, A.; Hinostroza, Y.; Casado, F.L. (Institute of Electrical and Electronics Engineers, 2021)
Tuberculosis is an age-old disease still threatening public health worldwide. The therapies available and improved hygienic conditions contribute to its control in well established sanitary systems. However, with the emergence of new respiratory infectious diseases, prevention and timely diagnosis is the more effective intervention. Peru is the second country with the highest number of tuberculosis cases in the world. Critical challenges regarding screening include biosafety compliance during sample collection, transport and arrival at diagnosis centers. We established needs for improvement and the critical stages of the current process of sputum sampling to propose a redesign of the container to improve its use by both the patients and health personnel. A collaborative effort with the feedback of the users and the manufacturers allowed us to optimize dimensions and geometry while improving closure and overall biosafety with a 20% reduction in the material cost.
Keywords: Aerosol; Container (type theory); Sample (material); Sputum; Materials science; Composite material; Tuberculosis; Chemistry; Medicine; Chromatography; Pathology; https://purl.org/pe-repo/ocde/ford#3.01.06